Diagnostic task realization by agent-based technics - Németh, Erzsébet; Piglerné Lakner, Rozália; Hangos, Katalin M. (Acta Agraria Kaposváriensis, 2006)
A multi-agent diagnostic system implemented in a Protégé-JADE-JESS environment interfaced with a dynamic simulator and database services is described in this paper. The proposed system architecture enables the use of a combination of diagnostic methods from heterogeneous knowledge sources. In order to facilitate the modularity and general applicability of the diagnostic system, ontologies are defined. The diagnostic system is demonstrated on a case study for diagnosis of faults in a granulation circuit based on HAZOP and FMEA analysis.